Development of mobile applications from existing Web-based enterprise systems. Issue 2 (15th June 2015) - Barroca Filho, Itamir de Morais; Aquino Júnior, Gibeon Soares
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to identify and propose strategies for development of mobile applications from Web-based enterprise systems and introduce a process called Metamorphosis. This process provides a set of activities subdivided into four phases – requirements, design, development and deployment – to assist in the creation of mobile applications from existing Web information systems. Design/methodology/approach – With the aim to provide a background to propose the Metamorphosis process, a systematic review was performed to identify strategies, good practices and experiences reported in the literature about creation of mobile applications. Findings – This paper identifies and proposes strategies for development of mobile applications from Web-based enterprise systems and introduces a process called Metamorphosis. Then, this process is applied for creation of SIGAA Mobile. Originality/value – The originality of this paper is the proposal of Metamorphosis process, that is, a process for development of mobile applications from Web-based enterprise systems.